TENTH-GRADE STUDENTS’ READING HABIT: (A Study Conducted at SMA Negeri 1 Tabukan Utara) - Grazella monary Bunok; Nihta V. F. Liando; Alloysius Rettob (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2022)
The present study tries to find out how students’ reading behavior in this digital era, especially during Covid 19 pandemic by assessing SMA students’ preference for online materials, their preferred language when reading online materials, the online reading habits of the students, and the amount of time they spend in reading online every day. The study was a survey that involved 44 tenth graders at SMA Negeri 1 Tabukan Utara in Likungan, Sangihe. The data were collected using a questionnaire adapted from Abidin, Pour-Mohammadi, & Jesmin (2011). The data collected were analyzed in percentages. Results of the analysis indicated that (1) the most common activities they are interested in are chatting, surfing the internet, and games, (2) concerning online reading materials, they prefer reading e-books, e-mail, stories, or novels, and comic strips/jokes. The majority of the respondents 89% prefer reading online reading materials in Indonesia, and (3) male respondents read more news, e-mails, and comic strips/jokes. Female respondents, on the other hand, preferred reading e-magazines, e-books, and movie reviews, and (4) the highest percentage of respondents (43%) spent 1-3 hours online daily reading. It is concluded that female respondents spent more time on online reading compared to their male counterparts.